PENGUATAN REGULASI PERLINDUNGAN INFRASTRUKTUR KRITIS DI INDONESIA TERHADAP ANCAMAN SERANGAN “DDOS” - Pradika, Alvin; Rachmania, Adinda Hilda; Widianti, Alifia; Astuti, Pudji (Smart Education, 2025)
Abstract: Strengthening regulations for the protection of critical infrastructure has become a primary urgency in Indonesia to address the threat of Distributed Denial of Service (DDoS) attacks. Critical infrastructure such as communication networks, financial systems, public services, and energy are increasingly vulnerable to these attacks due to their reliance on digital technologies. This study analyzes the vulnerability of Indonesia's critical infrastructure to DDoS attacks and formulates strategic steps and effective regulatory recommendations. Through a holistic approach that encompasses advanced technologies, adaptive regulations, and cross-sector collaboration, it is expected that Indonesia can enhance national resilience against cyber threats. The application of resilience theory and game theory also supports the development of better mitigation strategies. This research provides a foundation for strengthening cybersecurity regulations to maintain national economic, social, and security stability. Keyword: Regulation, Critical Infrastructure, DDoS, Cybersecurity, National Resilience, Resilience Theory, Game Theory Abstrak: Penguatan regulasi perlindungan infrastruktur kritis menjadi urgensi utama di Indonesia untuk menghadapi ancaman serangan Distributed Denial of Service (DDoS). Infrastruktur kritis seperti halnya jaringan komunikasi, sistem keuangan, layanan publik, dan energi semakin rentan terhadap serangan ini akibat ketergantungan pada teknologi digital. Penelitian ini menganalisis tingkat kerentanan infrastruktur kritis Indonesia terhadap serangan DDoS dan merumuskan langkah strategis serta rekomendasi regulasi yang efektif. Dengan pendekatan holistik yang mencakup teknologi canggih, regulasi adaptif, dan kolaborasi lintas sektor, diharapkan Indonesia mampu meningkatkan ketahanan nasional terhadap ancaman siber. Penerapan teori resiliensi dan teori game juga mendukung pengembangan strategi mitigasi yang lebih baik. Penelitian ini memberikan dasar untuk memperkuat regulasi keamanan siber demi menjaga stabilitas ekonomi, sosial, dan keamanan nasional. Kata kunci: Regulasi, Infrastruktur Kritis, DDoS, Keamanan Siber, Ketahanan Nasional, Teori Resiliensi, Teori Game.